Determination of Some Polychlorinated Biphenyls in River Tigris within Baghdad City - Khalid Waleed Salih Al-Janabi (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
A number of aqueous samples were collected from river Tigris in Baghdad city, enriched ~1000 times using solid phase extraction (SPE), then extracted the trace concentrations of some polychlorinated biphenyls (PCB) using an aqueous two-phase system (ATPS) composed of 1Methylpyridinium chloride [MePy]Cl and KH2PO4 salt. High performance liquid chromatography technique coupled with ultraviolet (HPLC-UV) is used for the quantification. Extraction under the optimized conditions of pH, solvent composition, duration and temperature has given with a yield of PCB about 91%. The limit of detection (LOD) and limit of quantification (LOQ) for analyses are 0.11-0.62 µg.L−1 and 2.67–3.43 µg.L−1 respectively with relative standard deviations (RSD) ranging from 2.9-7.6 %. The method can be applied for the analysis of other PCBs and bimolecular traces in aqueous media.